Epistemology of Values in Character Education, Mutual Cooperation, Religiosity, and Givmituplis Practice among Elementary Madrasah Students - Setiawan, Edi; Ardy Wiyani, Novan (International Proceedings of Nusantara Raya, 2024)
This study aims to reveal the epistemology of values in character education, particularly mutual cooperation and religiosity, among elementary madrasah students through the implementation of Givmituplis. Givmituplis is a learning method that integrates giving, asking, and expressing gratitude to instill character values. Through a qualitative case study, this research analyzes how the values of mutual cooperation and religiosity are formed and developed in the context of Givmituplis implementation. The results show that the Givmituplis practice has significant potential in shaping the character of mutual cooperation and religiosity among students. Through activities such as sharing, asking for help, and expressing gratitude, students learn to appreciate others, cooperate, and realize the importance of gratitude. These values are internalized within students and are reflected in their daily behaviors, both in school and at home. The epistemology of values in character education in this study indicates that the values of mutual cooperation and religiosity are formed through a complex internalization process. Students do not merely passively accept these values, but also actively construct their understanding and meaning of these values. This internalization process is influenced by various factors, such as social interaction with peers and teachers, as well as students' personal experiences in applying these values.